PERSPEKTIF EKONOMI DARI SISI TASAWUF ISLAM - Warno, Warno (JURNAL STIE SEMARANG, 2012)
Economics is one area of study that tried to solve the problem of the principle purposes of human life through penggemblengan all economic resources available to  berasaskan certain principles and theories in an economic system that is considered effective and efficient, it emerged as the world's limited resources so that the rules need to be able to meet of human needs. There is the word of  Alloh "There is no a moving creature on earth, but has been guaranteed by God's sustenance ..." and also "The depth in the search for food that has been guaranteed by God's will, and reduce what is required of you, including the nature of the show is basirah (eye care) are covered. "and" and Alloh will not change the fate of a people unless they change "of some of God's word can be concluded that humans have an obligation to try, but it does not guarantee results because of the business as an intermediary is not a critical success . People work and move the world by using a variety of science among them is the economics of it as an intermediary of a natural law that has been established by God